School counselors as agents of peace in the school: a systematic literature review - Wahyu Nanda Eka Saputra; Prima Suci Rohmadheny; Farid Suryanto (Institute of Advanced Engineering and Science, 2024)
Adolescence is a critical phase that can raise a problem, one of which is violence. This condition harms the dynamics of academic activities at school if they do not immediately find a solution. One party that has a central role in character development to suppress student violence is school counselors. This research is a systematic literature review that describes the counselor’s role as an agent of peace whose primary focus is to build a culture of peace in the school environment. The results showed that counselors used two pillars of service to create a culture of peace in schools, namely peace guidance and peace counseling. This paper discusses operational descriptions for each of the posts to build a culture of peace in the school environment. This results should serve as a reference for school counselors in supporting their programs to reduce violence in schools. Besides, this study also recommends conducting further research to create a guidance and counseling program to reduce violence among adolescents in schools.